Crowdsourcing: A new tool for policy-making? - TAEIHAGH, Araz (Institutional Knowledge at Singapore Management University, 2017)
Crowdsourcing is rapidly evolving and applied in situations where ideas, labour, opinion or expertise of large groups of people is used. Crowdsourcing is now used in various policy-making initiatives; however, this use has usually focused on open collaboration platforms and specific stages of the policy process, such as agenda-setting and policy evaluations. Other forms of crowdsourcing have been neglected in policy-making, with a few exceptions. This article examines crowdsourcing as a tool for policy-making and explores the nuances of the technology and its use and implications for different stages of the policy process. The article addresses questions surrounding the role of crowdsourcing and whether it can be considered as a policy tool or as a technological enabler and investigates the current trends and future directions of crowdsourcing.